2018
DOI: 10.1039/c8nr03612h
|View full text |Cite
|
Sign up to set email alerts
|

Transient DNA damage following exposure to gold nanoparticles

Abstract: Due to their interesting physicochemical properties, gold nanoparticles (Au-NPs) are the focus of increasing attention in the field of biomedicine and are under consideration for use in drug delivery and bioimaging, or as radiosensitizers and nano-based vaccines. Thorough evaluation of the genotoxic potential of Au-NPs is required, since damage to the genome can remain undetected in standard hazard assessments. Available genotoxicity data is either limited or contradictory. Here, we examined the influence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 60 publications
5
36
0
Order By: Relevance
“…[38][39][40] In recent years, exposure to gold nanoparticles has been reported to cause transient DNA damage due to the generation of alkali-labile sites and oxidative stress with a decrease in glutathione. 41,42 However, the phosphorylation level of H2A.X showed no change after treatment with U2-AuNP 24 hr. We considered that this phenomenon might be caused by a long U2-AuNP treatment time since DNA double-strand breaks (DSBs) happen within several hours.…”
Section: Discussionmentioning
confidence: 95%
“…[38][39][40] In recent years, exposure to gold nanoparticles has been reported to cause transient DNA damage due to the generation of alkali-labile sites and oxidative stress with a decrease in glutathione. 41,42 However, the phosphorylation level of H2A.X showed no change after treatment with U2-AuNP 24 hr. We considered that this phenomenon might be caused by a long U2-AuNP treatment time since DNA double-strand breaks (DSBs) happen within several hours.…”
Section: Discussionmentioning
confidence: 95%
“…The rationale behind utilizing 42 nm GNP in this experiment was based on a study by Chitrani's group that demonstrated 50 nm GNPs exhibited the highest radiosensitization in HeLa cells compared to 14 and 74 nm GNPs when irradiated with 220 kVp X-rays; DEF of 1.43 compared to 1.2 and 1.25, respectively [21]. In addition, various reports have shown the relative safety of GNPs in the range of 20-50 nm in different cell lines [22,23]. A recent in vitro study demonstrated no GNP-associated toxicity on HepG2 cells when incubated with 20 and 50 nm GNPs [24].…”
Section: Discussionmentioning
confidence: 99%
“…79 The controversial findings for the genotoxicity of Au-NPs may be due to the fact that a repair of DNA damage may also occur after Au-NP exposure. 80 We can only speculate on the mechanism of the genotoxicity induced by the 30 nm-sized AuNPs in this study. Although our 30 nm-sized citrate-stabilized Au NPs are too large to penetrate the nucleus, they may nevertheless be able to generate ROS in the cytoplasm which could then induce oxidative damage in the nucleus.…”
Section: Discussionmentioning
confidence: 80%